Collateral lending: Are there alternatives for the Kenyan banking industry? - Mary Karumba; Martin Wafula (Kenya Bankers Association (KBA), 2012)
Credit risk is perhaps the oldest and most challenging risk for banks. The risk emanates from the probability that borrowers will default on terms of debt, subsequently putting the capital of a bank in jeopardy. This concern has resulted in several attempts to manage the exposure of banks to credit risk, the most notable one being the Basel-II accord - later revised to Basel-III. The Basel guidelines aim at entrenching strict culture of managing inherent credit risk by financial institutions. Kenyan banks, like other financial institutions elsewhere, face the same problem and rely heavily on collateral lending which is a traditional instrument of providing security against loan advances. Although collateral lending gives lender some confidence, it has serious shortcomings. Notably, it hampers competition and limits lending activity especially if the banking sector demonstrates over-reliance on it. This study used time series data, deploying cointegration and error correction techniques to identify a long-run model for determination of bank lending behavior in Kenya. Evidence of over-reliance on collateral lending by the banking sector in Kenya is found, which can be attributed to less attention given to other credit mitigation measures by banks. The study also reviews other credit mitigation measures like credit referencing which has been introduced in the market recently and credit risk transfer which has not been considered in Kenya. We conclude that deepening the use of credit referencing, and introduction of credit risk transfer instruments - most basic of which is credit derivatives - could increase lending activity so long as the necessary institutional capacity, regulation and oversight are addressed well in advance.
Keywords: 330